Indigenous Knowledge in Education: A Study among Paniya Tribes in Kerala. - Manojan K.P. (Journal of Social Work Education and Practice, 2023)
In the context of the marginalised sections, education is claimed to be the weapon for their liberation and an agency that enhance their radical expressions and negotiations. But rendering of education is observed to be the reproduction of certain hegemonic power structure in the society. In this context, present study examines the relevance of indigenous knowledge in tribal education.